Hematopoiesis, biochemical and antioxidant parameters of blood of pigs consuming organic compounds of trace elements (Cu, Mn, Zn, Fe) in mineral feed supplement - V. Vlizlo; D. Ostapiv (Regulatory Mechanisms in Biosystems, 2025)
Development of mineral supplements containing necessary trace elements is essential for swine farming. Therefore, the o b jective of our study was to analyze the peculiarities of the influence of organic compounds of trace elements (copper, manganese, zinc, iron) on hematopoiesis, biochemical and antioxidant blood parameters of pigs. The experiment was conducted on three groups of pigs – one control and two experimental. The control group received a feed supplement with inorganic sulfate forms of trace elements (Cu, Mn, Zn, Fe). The pigs of the experimental groups – instead of inorganic salts of trace elements – were given a newly developed organic complex of trace elements (Cu, Mn, Zn, Fe) bonded using N-PEGylated glutamic acid as their feed supplement. The content of trace elements in the feed supplement of the experimental groups was lower than that in the control group. In particular, the concentrations of Cu, Mn, Zn, and Fe in Group 1 were lower by 51%, 42%, 20%, and 36%, respectiv e ly, whereas Cu, Mn, Zn, and Fe in Group 2 were lower by 48%, 39%, 17%, and 33%, respectively. Despite the low – compared with control group – contents of copper, manganese, zinc, and iron in organic form, the experimental animals were found to have improved hematopoiesis, metabolism, and antioxidant protection. The formation of erythrocytes and hemoglobin in the exper i mental pigs was stable, or even higher. The contents of total protein and its fraction, glucose, and total cholesterol in blood serum of the animals were at the physiological level throughout the intake of organic trace elements. The activities of the enzymes a s partate aminotransferase, alanine aminotransferase, and gamma-glutamyl transferase in blood serum were within the normal range and remained largely consistent across the three groups. The activity of the antioxidant-defense enzymes (superoxide di s mutase, glutathione peroxidase, and catalase) in blood of the pigs that received the trace elements in organic form were stable throughout the experiment and were consistent with the formation of lipid peroxidation products (malondialdehyde). In the f u ture, it would be practical to determine the effects of the complex of trace elements with N-PEGylated glutamic acid on the state of metabolism in the muscular tissue, productive parameters, and release of the elements with feces.